2020
DOI: 10.1097/md.0000000000019202
|View full text |Cite
|
Sign up to set email alerts
|

Can diffusion weighted imaging be used as an alternative to contrast-enhanced imaging on magnetic resonance enterography for the assessment of active inflammation in Crohn disease?

Abstract: The present study aimed to investigate the potential use of T2-weighted sequences with diffusion weighted imaging (DWI) in magnetic resonance (MR) enterography instead of conventional contrast-enhanced MR imaging (MRI) sequences for the evaluation of active inflammation in Crohn disease. Two-hundred thirteen intestinal segments of 43 patients, who underwent colonoscopy within 2 weeks before or after MR enterography were evaluated in this retrospective study. DWI sequences, T2-weighted sequences, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
7
0
4
Order By: Relevance
“…The specificity was somewhat higher than in our study (97.9 %). However, the examination was performed at 3 Tesla and only involved the colon and terminal ileum 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity was somewhat higher than in our study (97.9 %). However, the examination was performed at 3 Tesla and only involved the colon and terminal ileum 7 .…”
Section: Discussionmentioning
confidence: 99%
“…2 zu sehen. Statistik Alle erfassten Parameter und Ergebnisse wurden mithilfe der Statistik-Software SPSS, IBM Statistics, Version 20.0.0 ausgewertet.Die Werte der beiden Seo-Scores wurden in einem Scatterplot gegeneinander aufgetragen und in Subtraktionshistogrammen dargestellt (▶ Abb [3][4][5][6][7][8][9]…”
unclassified
“…Multiple disease scoring systems were used. The modified Baron score was used in three studies [13][14][15], the Simple Clinical Colitis Activity Index (SCCAI) in two studies [13,16], the CD Endoscopic Index of Severity (CDEIS) in two studies [17,18], Crohn's Disease Activity Index (CDAI) in three studies [19][20][21], Pediatric Crohn's Disease Activity Index (PCDAI) in one study [22], Mayo Endoscopic Subscore (MES) in two studies [16,23], Truelove and Witts score in two studies [21,24], and the Simple Endoscopic Score for CD (SES-CD) was used in four studies [13,[25][26][27] The performance of MRI and US was assessed in 24 and 17 studies, respectively, while CT was assessed only in two studies hence excluding this imaging modality from the meta-analyses. The diagnostic test values (TP, FP, TN, and FN) of the colonic segments and the sensitivity and specificity values were not presented in all the included studies.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…In addition, some studies have used bowel preparation protocols, which can affect the quality of bowel visualization. 3,4 However, this practice is currently not a clinical standard as evident from a recent survey of academic institutions. 5 Moreover, a recent study by Sinha et al has suggested that bowel cleansing is not necessary since MRE primarily focuses on the small bowel, which is unaffected by a loaded colon.…”
mentioning
confidence: 99%
“…For high‐quality MRE, adequate luminal distension and visualization of bowel wall enhancement is vital, which is achieved by the patient ingesting a regimen of liquids, including a hyperosmolar liquid and a biphasic oral contrast agent, and also administration of intravenous gadolinium. In addition, some studies have used bowel preparation protocols, which can affect the quality of bowel visualization 3,4 . However, this practice is currently not a clinical standard as evident from a recent survey of academic institutions 5 .…”
mentioning
confidence: 99%